2013
DOI: 10.1080/01635581.2014.851712
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Prostate Cancer Risk: Report from the Population Based ULSAM Cohort Study of Swedish Men

Abstract: Dietary pattern analyses have increased the possibilities to detect associations between diet and disease. However, studies on dietary pattern and prostate cancer are scarce. Food intake data in the Uppsala Longitudinal Study of Adult Men cohort was determined by 7-day food records. Adherence to a modified Mediterranean Diet Score (mMDS) and a low carbohydrate-high protein (LCHP) score were grouped as low, medium, or high in the whole study population (n = 1,044) and in those identified as adequate reporters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 52 publications
3
40
0
2
Order By: Relevance
“…Prospective studies investigating the relation of dietary pattern and PCa incidence have reported inconsistent results (8, 18-21). Three cohorts evaluating dietary patterns using principal component analysis (as we did in this study) found no association between the data-derived patterns and PCa risk (8, 19, 20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies investigating the relation of dietary pattern and PCa incidence have reported inconsistent results (8, 18-21). Three cohorts evaluating dietary patterns using principal component analysis (as we did in this study) found no association between the data-derived patterns and PCa risk (8, 19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Three cohorts evaluating dietary patterns using principal component analysis (as we did in this study) found no association between the data-derived patterns and PCa risk (8, 19, 20). Using index-based methods, studies indicated that alternate or modified Mediterranean Diet Score were not appreciatively associated with risk of PCa (18, 21), whereas the Healthy Eating Index-2005 and Alternate Healthy Eating Index-2000 were significantly associated with lower risk of developing incident PCa (18, 21). However, studies on risk of total PCa are expected to differ from those that focus on disease-specific mortality, due to the high incidence of indolent PCa in populations with PSA screening.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer has an important genetic component (3). Besides, lifestyles especially dietary factors are also reported to influence prostate cancer risk (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In the ULSAM study, those who adhered more closely to a low-CHO, high-protein diet were associated with a lower risk of prostate cancer (67).…”
Section: Dietary Patterns and Prostate Cancer Riskmentioning
confidence: 99%